2010
DOI: 10.1108/09596111011035981
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among hedonic and utilitarian values, satisfaction and behavioral intentions in the fast‐casual restaurant industry

Abstract: PurposeThe paper aims to examine the relationships among hedonic and utilitarian values, customer satisfaction and behavioral intentions in the fast‐casual restaurant industry.Design/methodology/approachThe measures were developed based on a thorough review of the previous literature. Questionnaires were collected in classroom settings at a mid‐western university in the USA. Anderson and Gerbing's two‐step approach was employed to assess the measurement and structural models.FindingsThe findings indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
306
3
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(413 citation statements)
references
References 55 publications
41
306
3
21
Order By: Relevance
“…Moreover, satisfaction of a consumer can be considered as alternation of his/her attitude which is caused by the experience of consumption (Jiu & Da, 2009). Hunt (1977) defined customer satisfaction as assessment of consumption experience at the minimum level of appropriateness which assumed to be (Ryu et al, 2010;Hanzaee & Rezaeyeh, 2013). thus: H3: With increasing in innovation of product, customer satisfaction will be increased.…”
Section: Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, satisfaction of a consumer can be considered as alternation of his/her attitude which is caused by the experience of consumption (Jiu & Da, 2009). Hunt (1977) defined customer satisfaction as assessment of consumption experience at the minimum level of appropriateness which assumed to be (Ryu et al, 2010;Hanzaee & Rezaeyeh, 2013). thus: H3: With increasing in innovation of product, customer satisfaction will be increased.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Experts and researchers have always been trying to provide a complete conception of value. A comprehensive literature review has specified a concept that perceived value is what a consumers attain for what they give, or the consumer's evaluation of the advantage that provided by a product or services for him/her (Ryu et al, 2010;Hanzaee & Rezaeyeh, 2013).…”
Section: Hedonic Valuementioning
confidence: 99%
“…The findings are inconsistent with those of previous research conducted in the hospitality and tourism industry. For instance, the results obtained by Ryu et al [54] identified utilitarian value as a stronger indicator of consumer satisfaction than hedonic value in the restaurant sector. The findings of Ha and Jang [53] support this result; they postulated that utilitarian value is a stronger indicator of consumer satisfaction than hedonic value in Korean restaurants in the United States.…”
Section: Discussionmentioning
confidence: 92%
“…This finding was also confirmed by a study conducted with Korean participants at casual fast food restaurants in Korea. Ryu, et al [54] reported that utilitarian value (i.e., convenience, accessibility, and reasonable price) significantly affected customer satisfaction and intention to revisit, compared with staff service, friendliness, and taste of food. In addition, Park [55] analyzed the differences in the relative effects of restaurant uniqueness and functional image on restaurant preference through the moderating effect of hedonic and utilitarian shopping motivations.…”
Section: Hedonic and Utilitarian Valuesmentioning
confidence: 99%
“…Kako bi zadržala potrošače i obezbedila njihovu lojalnost, preduzeća moraju biti fokusirana na isporuku superiorne vrednosti i postizanje visokog nivoa satisfakcije (Stanković & Djukić, 2011). U brojnim studijama potvrđena je pozitivna veza između zadovoljstva i lojalnosti potrošača (Han & Ryu, 2009;Kivela et al, 1999;Ryu et al, 2010). Međutim, ovu tvrdnju ne treba generalizovati, jer se javljaju situacije u kojima povećanje nivoa satisfakcije ne vodi ka lojalnosti.…”
Section: Odnos Kvaliteta Restoranske Usluge I Satisfakcije Potrošačaunclassified